2013
DOI: 10.1016/j.pnpbp.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The antinociceptive effect of reversible monoamine oxidase-A inhibitors in a mouse neuropathic pain model

Abstract: Neuropathic pain is a debilitating condition that is often resistant to common analgesics, such as opioids, but is sensitive to some antidepressants, an effect that seems to be mediated by spinal cord 5-HT3 receptors. Because the analgesic potential of monoamine oxidase-A (MAO-A) inhibitors is understudied, we evaluated the potential antinociceptive effect of the reversible MAO-A inhibitors moclobemide and 2-(3,4-dimethoxy-phenyl)-4,5-dihydro-1H-imidazole (2-DMPI) in a mouse neuropathic pain model induced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
5
18
0
Order By: Relevance
“…We then evaluated the effect of chronic fisetin treatment on the MAO-A and MAO-B activities in mouse spinal cord. As shown in Table 2, the activity of MAO-A but not MAO-B increased markedly when the mice were rendered neuropathic by CCI-lesion, which is in congruent with a recent study by Villarinho et al31. Chronic treatment of CCI mice with fisetin (5, 15 and 45 mg/kg) dose-dependently inhibited the escalated spinal MAO-A activity, and the MAO-A activity is reduced to levels observed in non-injured animals following the treatment with fisetin at the dose of 45 mg/kg.…”
Section: Resultssupporting
confidence: 92%
“…We then evaluated the effect of chronic fisetin treatment on the MAO-A and MAO-B activities in mouse spinal cord. As shown in Table 2, the activity of MAO-A but not MAO-B increased markedly when the mice were rendered neuropathic by CCI-lesion, which is in congruent with a recent study by Villarinho et al31. Chronic treatment of CCI mice with fisetin (5, 15 and 45 mg/kg) dose-dependently inhibited the escalated spinal MAO-A activity, and the MAO-A activity is reduced to levels observed in non-injured animals following the treatment with fisetin at the dose of 45 mg/kg.…”
Section: Resultssupporting
confidence: 92%
“…We then evaluated the spinal MAO-A and MAO-B activities following repetitively oral isorhynchophylline treatment. As shown in Table 1, Neuropathic mice showed escalated activity of MAO-A but not MAO-B compared with sham mice, which is consistent with a previous study by Villarinho et al (2013). Following repetitive oral treatment, isorhynchophylline with doses ranging from 5 to 45 mg/kg dose-dependently inhibited the escalated spinal MAO-A activity in neuropathic mice (F 3,38 = 14.2, p = 0.0072), and at the high dose of 45 mg/kg the MAO-A activity is reduced to the level essentially equivalent to that of sham mice.…”
Section: Repetitive Isorhynchophylline Treatment Increased Spinal Monsupporting
confidence: 91%
“…Several studies investigated the effects of MAO inhibitors on neuropathic pain (Apaydin et al, 2001;Villarinho et al, 2013;Villarinho et al, 2012). Moclobemide was investigated in rats (Apaydin et al, 2001) and mice (Villarinho et al, 2013) which showed an increased mechanical paw withdrawal threshold and both studies concluded that moclobemide might be a treatment alternative for symptoms of peripheral neuropathic conditions.…”
Section: Pain Treatmentmentioning
confidence: 99%
“…Moclobemide was investigated in rats (Apaydin et al, 2001) and mice (Villarinho et al, 2013) which showed an increased mechanical paw withdrawal threshold and both studies concluded that moclobemide might be a treatment alternative for symptoms of peripheral neuropathic conditions. In the mouse model, the same authors applied the MAO-B inhibitor selegiline on postoperative and neuropathic pain and concluded that MAO-B exerts a critical role in the development in these pain conditions.…”
Section: Pain Treatmentmentioning
confidence: 99%